2015
DOI: 10.1177/0885328215590967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-temperature ethylene oxide and electron beam sterilization on the in vitro and in vivo function of reconstituted extracellular matrix-derived scaffolds

Abstract: Reconstituted extracellular matrix (ECM) -derived scaffolds are commonly utilized in preclinical tissue engineering studies as delivery vehicles for cells and growth factors. Translation into clinical use requires identifying a sterilization method that effectively removes bacteria but doesn’t harm scaffold function. To determine effectiveness of sterilization and impact on ECM scaffold integrity and function low temperature ethylene oxide and 15kGy electron beam irradiation techniques were evaluated. Scaffold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Alternative methods of terminal sterilization include ethylene oxide 9 (ETO) and high-energy radiation (electron beam or g radiation), both of which can have a negative effect on the ECM bioscaffolds. ETO can react with the free amine groups of collagen, affecting the mechanical properties of ECM bioscaffolds, and high-energy radiation damages protein chains and promotes the formation of free radicals (Proffen et al 2015). Supercritical CO 2 sterilization 10 has been investigated for sterilization of collagen scaffolds and showed minimal compromise of mechanical properties (Bernhardt et al 2015).…”
Section: Ecm Bioscaffold Sterilizationmentioning
confidence: 99%
“…Alternative methods of terminal sterilization include ethylene oxide 9 (ETO) and high-energy radiation (electron beam or g radiation), both of which can have a negative effect on the ECM bioscaffolds. ETO can react with the free amine groups of collagen, affecting the mechanical properties of ECM bioscaffolds, and high-energy radiation damages protein chains and promotes the formation of free radicals (Proffen et al 2015). Supercritical CO 2 sterilization 10 has been investigated for sterilization of collagen scaffolds and showed minimal compromise of mechanical properties (Bernhardt et al 2015).…”
Section: Ecm Bioscaffold Sterilizationmentioning
confidence: 99%
“…A hydrogel of extracellular matrix proteins was made by aseptically harvesting bovine connective tissue from the knee capsule, decellularization with a detergent solution and solubilization using pepsin in hydrochloric acid as previously described. 25 The resulting gel was neutralized using a buffer containing HEPES, sodium hydroxide, and calcium chloride to a pH of 7.4 and kept at 4˚C until use. At time of injection, animals were anaesthetized and 50 ml of blood was drawn from the tail vein of the rat and mixed with acidcitrate-dextrose (ACD) in a ratio of 10:1.…”
Section: Preparation and Injection Of The Extracellular Matrix Gel/ Amentioning
confidence: 99%
“…The authors found that this method of sterilization was effective and had no significant influence on in vivo function of the scaffolds. Moreover, Proffen et al after an animal study showed that low-temperature ethylene oxide and electron beam irradiation were acceptable methods of sterilization of reconstituted extracellular matrix-derived scaffolds [ 28 ]. The slight modification of in vitro scaffold properties did not significantly alter biologic reactions of the surrounding tissues in vivo.…”
Section: Main Textmentioning
confidence: 99%
“…The BEAR scaffold was manufactured at Boston Children’s Hospital and completed all biocompatibility and sterility testing prior to use in the clinical study [ 36 , 37 ]. The scaffold comprised extracellular matrix proteins, including collagen, that were obtained from bovine tissue [ 28 ].…”
Section: Main Textmentioning
confidence: 99%